High-efficiency Generation of Multiple Short Noncoding RNA in B-cells and B-cell-derived Extracellular Vesicles - Gonzalo Almanza; Maurizio Zanetti (Elsevier, 2015)
Short noncoding (snc)RNAs are important new players in the landscape of biologics with therapeutic potential. Recently, we reported on a new method for the synthesis and delivery of snc RNA in B-cells transfected with plasmid DNA. Here using the same approach, we demonstrate that B-cells can be programmed for the enforced biogenesis and synchronous release of multiple sncRNAs. Our data show that this goal is feasible and that multiple sncRNA are released in the extracellular compartment in amounts comparable to those from B-cells programmed to express and secrete one scnRNA only. Furthermore, we found that the cargo of extracellular vescicles (EVs) isolated from programmed B-cells is remarkably enriched for multiple sncRNA. On average, we found that the content of multiple sncRNAs in EVs is 3.6 copynumber/EV. Collectively, we demonstrate that B-cells can be easily programmed toward the synthesis and release of multiple sncRNAs, including sncRNA-laden EVs, efficiently and specifically.